Scientific ways of new orchard plantation - Singh, Sarvpriya; Bassi, Palwinder Singh; Dhaliwal, Ajitpal Singh (Indian Farming, 2021)
An orchard is a long-time venture and mistakes committed at the initial stages of orchard establishment are very difficult to correct at later phases as they cause an unbearable loss to the growers. Orchardist can prevent many risks through adopting appropriate orchard establishment practices like soil and climate, planning, site selection, provision of irrigation channels, paths and roads, buildings and plantation at suitable spacing, and procurement of healthy nursery plants. It is necessary to know the scientific background and behaviour of the fruit plant and their adaptability to a wide range of climatic condition. The main aim of this article is to minimize the losses for new growers who want to plan a new orchard plantation and their care and maintenance.